THE REALITY OF VENTURE CAPITAL COMPANIES IN ALGERIA AND THEIR ROLE IN FINANCING ENTREPRENEURSHIP: ICOZIA COMPANY AS A MODEL (Lex localis - Journal of Local Self-Government, 2025)
This study aims to introduce venture capital as a newly developed tool for financing projects in Algeria in particular, through examining the contribution of Ecozia Company in this field.Ecozia Company is considered one of the most important venture capital companies in Algeria, having achieved a certain degree of success over the last decade, due to its flexibility in financing projects across various sectors compared to other companies, with a focus on industrial projects exceeding 50%.